Analisis Hukum terhadap Tindak Pidana Korupsi di Bidang Konstruksi dalam Pembangunan Gedung NTT Fair: (Studi Kasus Putusan Nomor 42/Pid.Sus-TPK/2019/PN.Kpg) - Filmon Lopo; Karolus Kopong Medan; Rudepel Petrus Leo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Procurement of Government Goods / Services is a government spending mechanism that plays an important role in the utilization of state budget. Construction services are sectors that play an important role in Indonesia's development. Through this sector, the physical progress of development can be seen directly. In practice in general the implementation of procurement of goods / services Government construction often occurs problems, among other things, violations of both the Procurement Procurement procedure and the infringement that are detrimental to the State or the criminal act of corruption perpetrated by the organization of procurement of goods / services Construction. The purpose of this study is to determine the legal arrangements for the procurement of goods / services of construction after Perpres No. 4 Tahun 2015 and To know how the implementation of the application of criminal law of corruption in the field of goods / construction services on the decision No. 42/Pid.sus-TPK/2019/PN.KPG. This research is a normative research using primary data and secondary data. The data were collected through interview method and literature study which then analyzed qualitatively and presented descriptively. Based on the results of research has been done, the authors concluded that (1) has been arranged various legal instruments related to the implementation of procurement of goods / government construction services starting from the Act up to the Presidential Decree as a technical arrangement; and (2) the application of criminal law of corruption to the decision No. 42Pid.sus TPK/2019/PN.KPG has been in accordance with the provisions the provisions of the Act constitution. 20 year 2001 jo constutition No 31 Tahun 1999 about Eradiction Criminal Act of Corruption.